PENGARUH SIZE, WEALTH, INTERGOVERNMENTAL REVENUE, DAN PAJAK DAERAH TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH DENGAN BELANJA MODAL SEBAGAI VARIABEL MODERASI - Paramitha Salsabila Abbas (2023)
This research is a quantitative research conducted to test and prove the relationship between the influence of size, wealth, intergovernmental revenue, and local taxes on the financial performance of local governments moderated by capital expenditure. The sample in this study was 469 LKPD of district/city from all over Indonesia for the 2021 period which had been audited and selected using a purposive sampling method. The analysis technique used is path analysis using Smart PLS 3 software with a significance level of 5%. The results of the test show that wealth, intergovernmental revenue, and local taxes have an effect on local government financial performance, while size has no effect on local government financial performance. In the moderation relationship, capital expenditure is only able to moderate the relationship between regional taxes and local government financial performance, while capital expenditure is not able to moderate the relationship between size, wealth, and intergovernmental revenue on local government financial performance.